Increasing Knowledge About Infection Prevention in Post-Operative Wounds - Lestari, Enur Rara; Trihapsari, Nadia; Sutarni, Sri; Hermawati, Hermawati; Subagya, Nanang Legawa (CV. Rayyan Dwi Bharata, 2025)
The increasing incidence of both acute and chronic wounds is a significant global health issue with the prevalence of wound patients reaching 3.50 per 1000 population in the US. The most common types of wounds include surgical wounds, leg ulcers and decubitus wounds. In Indonesia, the prevalence of wounds increased from 8.2% to 9.2%. At the Surgery Clinic of Dr. Moewardi Hospital Surakarta, patients and families do not know about wound infection prevention. To improve knowledge, health education was conducted regarding the definition of wounds, signs of infection, and how to prevent infection. The method used in health education is question and answer, and measuring the level of knowledge by giving a questionnaire containing 10 questions related to the definition of wounds, infection, and how to prevent infection.